Por uma leitura crítica da categoria consciência na obra “Educação como prática da liberdade” de Paulo Freire - Batalha, Douglas (Universidade Federal de São Carlos, 2022)
The aim of this work is to present, discuss and critically position itself regarding the category consciência in the work “Educação como prática da liberdade” (1967) by Paulo Freire (1921– 1997). For that, a qualitative approach will be used with emphasis, through bibliographic and documental survey, as well as complementary bibliography. The text will be guided by the guiding question: why does understanding the category consciência require a critical reading of the work “Educação como prática da liberdade” and, consequently, of freirean thought? The results obtained, in addition to the writing of this monograph, indicated that the critical resumption of the work studied is important and, in particular, the category consciência, since the observance of the conditions of writing and circulation of the book in its particular time and historical space , in addition to the arrangement itself and internal and intrinsic relationships to the text, better allow the scope and relationship in perspective of this with the development of freirean thought.
For a critical reading of the category conscience in the “Educação como prática da liberdade” by Paulo Freire
Keywords: Consciência; Paulo Freire; Educação como Prática da Liberdade; Conscience; Paulo Freire; Education as a Practice of Freedom; CIENCIAS HUMANAS::EDUCACAO